Systematic Literature Review: Penerapan Model Challenge Based Learning (CBL) pada Pembelajaran IPA - Ni Kadek Juniawati; I Wayan Redhana; I Nyoman Tika (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to conduct a systematic literature review through a Systematic Literature Review regarding the application of the Challenge Based Learning (CBL) model in Natural Science (IPA) learning. CBL is a pedagogical approach that involves students in solving real-world challenges, encouraging active learning, collaboration, and the development of 21st-century skills. The method used in this study is a Systematic Literature Review (SLR) using the PRISMA technique with keywords namely Challenge Based Learning (CBL), 21st-Century Skills, and Science Learning. The inclusion criteria of this study are articles discussing the CBL learning model, elementary, junior high, and high school education levels, full-text access, original research (development, qualitative, quantitative, and CAR), published within the 2020-2025 range (the last 5 years), while the exclusion criteria are articles outside the inclusion criteria. By analyzing relevant literature, this study identifies the characteristics, effectiveness, and challenges in implementing CBL in science learning at various levels of education. The review results indicate that CBL has great potential to improve students' learning motivation, conceptual understanding, critical thinking skills, and problem-solving abilities in science. However, CBL implementation also faces several obstacles, such as the need for thorough teacher preparation, resource availability, and relevant challenge design. The implications of this research are expected to provide guidance for educators, researchers, and curriculum developers in effectively integrating CBL into science learning.